Student-generated socioscientific analogies effects on scientific literacy and appreciation of biology - Reyes, Vincent Paul Roque (College of Education, University of the Philippines Diliman, 2019)
The study aimed to determine the effects of student-generated socioscientific analogies (SGSSA) on students scientific literacy and appreciation of Biology. It involved 94 grade eight students at a national high school in Cabiao, Nueva Ecija during the third quarter of School Year 2016-2017. Both experimental and control groups were composed of 47 students each, the former exposed to the Students Generated Socioscientific Analogies Mode of Instruction (SGSSA MI), while the latter was taught with the Direct Mode of Instruction (DMI). The research instruments used were Scientific Literacy Test (SLT) and Appreciation of Biology Scale (ABS). Two-tailed t-test for independent samples was used to check the comparability of the two groups in terms of scientific literacy and appreciation of biology prior to the treatment. One-tailed t-test for independent samples was done on the mean posttest scores in the SLT and ABS to find out if there was a significant difference between the two groups after the treatment. One-tailed paired samples t-test was used to compare the mean pretest and posttest scores in SLT and ABS to determine if each group had significant improvement after the treatment. Simple linear regression was used to assess if the students appreciation of Biology positively predicts scientific literacy. All hypotheses were tested at 5.0 level of significance. Results revealed that there was no significant difference in scientific literacy and appreciation of Biology between SGSSA MI and DMI groups. Through linear regression, it was found that appreciation of Biology does not positively predict scientific literacy. Lately, students appreciate Biology in terms of anxiety since in tolerable amounts; it brings forth better memory retention. In addition, it increases motivation and alertness especially when faced with danger.